Applicability of SIDRA for heterogeneous traffic - Elsayed, Mohamed Ahmed Abdelhadi (2013)
Delay is an important factor in the optimization of traffic signals and the determination of the level of service of a signalized intersection. Various models have been developed to estimate delay to traffic at signalized intersections. All the models are based on homogeneous traffic conditions; these models may not estimate the delays satisfactorily under heterogeneous traffic conditions. The main objective of this study is to evaluate the applicability of Signalized Intersection Design Aid (SIDRA) Software which is widely used for estimating delay at signalized intersections in Malaysia. This is because SIDRA considers only two main types of vehicles, i.e. passenger car and heavy good vehicles. Traffic control delays for a range of traffic volumes and compositions were collected at a selected signalized intersection. The associated traffic volumes were used to evaluate the delay estimated by SIDRA software were compared with the corresponding delays measured at selected sites. The results show that the delay estimated by SIDRA software is higher than the observed delay. This implies that the analysis of delay for heterogeneous traffic cannot be based on existing homogeneous traffic delay models